Moderate-Intensity Intermittent External Volume Expansion Optimizes the Soft-Tissue Response in a Murine Model. Issue 4 (April 2017) - Giatsidis, Giorgio; Cheng, Liying; Facchin, Federico; Haddad, Anthony; Lujan-Hernandez, Jorge; Lancerotto, Luca; Nabzdyk, Christoph Gunther; Matsumine, Hajime; Orgill, Dennis P.
Abstract : Background: Intermittent external volume expansion using suction enhances the vascular network of soft tissues, possibly increasing fat graft survival. However, the optimal kinetics of application have not been determined. Based on their previous experience, the authors hypothesized that moderate-intensity intermittent external volume expansion application may further enhance both the angiogenic and adipogenic potential. Methods: Fifty 12-week-old wild-type mice were assigned to five experimental groups ( n = 10 per group) and underwent five different intermittent applications of external volume expansion (i.e., single-application control, low-intensity, moderate-intensity, and two groups of high-intensity). Five days after the final stimulation, skin biopsy specimens were obtained from stimulated and contralateral nonstimulated areas. Microscopic sections were analyzed for angiogenesis, skin remodeling, and adipogenesis. Results: Moderate-intensity intermittent stimulation (0.5 hour, 6 times/day for 5 days at −25 mmHg suction) almost doubled cutaneous vascular density (1.9-fold increase), induced skin thickening (1.9-fold increase), and expanded the subcutaneous tissue (2.3-fold increase) compared with control. External volume expansion kinetics did not affect tissue inflammation at 5 days after treatment. High-intensity intermittent stimulations also increased the density of blood vessels (1.6-fold increase compared with controls) but caused tissue damage, whereas low-intensity external volume expansion did not induce significant changes. Conclusion: Application of moderate-intensity intermittent external volume expansion optimizes induction of angiogenesis and adipogenesis in soft tissues without tissue damage, holding potential for time-effective recipient-site preconditioning before fat grafting. Abstract : Supplemental Digital Content is available in the text.